2018
DOI: 10.5713/ajas.17.0760
|View full text |Cite
|
Sign up to set email alerts
|

Applications of capacitation status for litter size enhancement in various pig breeds

Abstract: ObjectiveSeveral studies have reported the development of new molecular methods for the prognosis and diagnosis of male fertility based on biomarkers aimed at overcoming the limitations of conventional male fertility analysis tools. However, further studies are needed for the field application of these methods. Therefore, alternative methods based on existing semen analysis methods are required to improve production efficiency in the animal industry.Methodswe examined the possibility of improving litter size i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Recently, Kwon et al used CTC combined with H33258 staining to examine sperm capacitation status and applied it to evaluate boar fertility, showing an increased litter size in a field trial [ 32 ]. They also showed that combined H33258/CTC staining might be used to predict male fertility in various pig breeds [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kwon et al used CTC combined with H33258 staining to examine sperm capacitation status and applied it to evaluate boar fertility, showing an increased litter size in a field trial [ 32 ]. They also showed that combined H33258/CTC staining might be used to predict male fertility in various pig breeds [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Semen samples were collected after sexual maturation and diluted as described above. AI was performed by professional technicians from Sunjin Co. twice per estrus 32 , 65 , 66 . The inseminated sows were managed at 20 ± 5 °C with air circulation, 2:1 light/dark cycle, and adequate feed for pregnant sow during the experimental period.…”
Section: Methodsmentioning
confidence: 99%
“…The supernatant containing excess dye was discarded, and the pellet was resuspended in 100-µL PBS and 100-µL CTC solution (750-mM CTC in 5-µL buffer consisting of 20-mM Tris, 130-mM NaCl, and 5-mM cysteine at a pH of 7.4). The capacitation status was assessed using a fluorescence microscope (Nikon, Tokyo, Japan) for 100 spermatozoa per slide [30]. Incapacitated sperms were indicated by green fluorescence distributed uniformly over the entire sperm head, with or without a more robust fluorescent line at the equatorial segment.…”
Section: Capacitation and Acrosome Reactionmentioning
confidence: 99%